Profit with honor : the new stage of market capitalism - Yankelovich, Daniel (New Haven : Yale University Press, 2006)
This wise and optimistic book examines the rampant scandals that plague American corporations today and shows how companies can reverse the resulting climate of mistrust. By seizing the opportunity to address some of the nationsand the worldsmost serious problems, business can strengthen its reputation for integrity and service and advance to a new stage of ethical legitimacy. Daniel Yankelovich, a social scientist and an experienced member of the corporate boardroom, describes the toxic convergence of cultural and business trends that has led inexorably to corporate scandals. Yet he offers reassurance that opportunity exists for positive change. Creative business leaders can advance market capitalism to its next stage of evolution, building upon business norms that simultaneously emphasize the legitimacy of profit making and the importance of the care that companies give to employees, customers, and the larger society. The book asserts that American culture has abandoned its old tradition of enlightened self-interest, of doing well by doing good. A narrow legalism has taken over (I didnt break the law; therefore I didnt do anything wrong). Yankelovich argues that attempts to deal with such flawed ethical norms by means of more laws and regulations cannot succeed. He offers a series of case histories to show how and why stewardship ethics can strengthen individuals, corporations, the nation, and the world economy.
The wrong way to stop the scandals -- Screwed again -- Unenlightened self-interest -- Yesterday's versus today's ethical norms -- Two incomplete visions -- Unpacking stewardship ethics -- The vision of stewardship ethics -- What to do about shareholder value -- Restoring gatekeeper integrity -- Hummer versus hybrid.
Includes bibliographical references (pages 177-180) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Capitalism -- Moral and ethical aspects; Business ethics; Social responsibility of business; Capitalisme -- Aspect moral; Morale des affaires; Entreprises -- Responsabilité sociale; BUSINESS & ECONOMICS -- Business Ethics; Business ethics; Capitalism -- Moral and ethical aspects; Social responsibility of business; Ethik; Kapitalismus; Kapitalisme; Bedrijfsethiek; Sociaal bedrijfsbeleid